KINETIC, THERMODYNAMIC AND PARAMETRIC STUDIES OF OIL EXTRACTION FROM JATROPHA OILSEEDS - Sunday. U John; Philomena Igbokwe K.; Joseph Nwabanne T (International Journal of Innovations in Engineering Research and Technology, 2021)
The kinetics, thermodynamics, and effects of process variables on Jatropha seed oil (JO) extraction were investigated via soxhlet extraction using petroleum ether. The kinetic models investigated were power law, pseudosecond-order, parabolic-diffusion, pseudo-first-order, Elovich, and hyperbolic models. The process parameters studied include, the extraction temperature, average particle size, and time. The thermodynamics parameters such as Gibb free energy, enthalpy, and entropy were determined. It was found that oil extraction yield varied directly proportional to an increase in temperature and time but inversely proportional to an increase in particle size. The maximum oil yield of 39.5 % was obtained at the extraction conditions of 74 oC, 0.1 mm, and 180 min. The best fitted kinetic models in order of performance were hyperbolic, parabolic, elovich, and power-law models. The average values of the absolute average relative error (AARE), the sum of the squares of errors (SSE), root mean squared error (RMSE), standard deviation (SD), total sum of squares (SST), coefficient of determination (R2), adjusted-coefficient of determination (adj-R2), hybrid fractional error function (HYBRID%), the Marquardt’s percent standard deviation (MPSED%), and standard error of estimation (SEE) for power law as the best-fitted model is as follows: 0.0004, 0.4804, 0.0004, 6.72E-06, 16.6067, 96.8432, 96.4486, 0.0063, 0.0593, 0.0133, respectively. However, pseudo-second-order and pseudo-first-order models failed to give adequate fitting to the experimental data. The Gibb free energy, enthalpy, and entropy values of the Jatropha oil extraction process at 328K and 0.1mm were -3.53kJ/mol, 45.79kJ/mol, and 0.15kJ/mol, respectively, indicating endothermic, irreversible, and spontaneous process.